2013
DOI: 10.1248/bpb.b13-00127
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling for Identification of Potential Biomarkers in the Protective Effects of Modified Sinisan against Liver Injury in Dimethylnitrosamine Treated Rats

Abstract: Metabolomics is a new platform based on the comprehensive analysis of low molecular weight metabolites and provides a powerful approach to discover biomarkers in biological systems. Modified Sinisan (MSNS), a traditional Chinese medicine formula, displayed bright prospects in the prevention and therapy of liver injury. However, its molecular mechanism of hepatoprotective effects remains unclear. This paper was designed to explore the effects and potential mechanisms of MSNS against dimethylnitrosamine-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The liver is the principal site of the hydroxylation of phenylalanine to tyrosine and further tyrosine degradation. Previous studies have shown that metabolic disturbance of phenylalanine and tyrosine is responsible for many clinical disorders of livers [54,55]. In our study, the levels of phenylalanine and tyrosine in the DM groups were significantly less than those in the DM groups at the 5th and 9th weeks, indicating that phenylalanine and tyrosine metabolism were impaired during DM development.…”
Section: Liver Amino Acid Metabolism During Dm Developmentsupporting
confidence: 45%
“…The liver is the principal site of the hydroxylation of phenylalanine to tyrosine and further tyrosine degradation. Previous studies have shown that metabolic disturbance of phenylalanine and tyrosine is responsible for many clinical disorders of livers [54,55]. In our study, the levels of phenylalanine and tyrosine in the DM groups were significantly less than those in the DM groups at the 5th and 9th weeks, indicating that phenylalanine and tyrosine metabolism were impaired during DM development.…”
Section: Liver Amino Acid Metabolism During Dm Developmentsupporting
confidence: 45%
“…Serum Tyr concentrations are significantly increased in patients with liver injury [36]. Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…This prescription consists of four herbal medicines: Bupleuri Radix, Paeoniae Alba Radix, Aurantii Immaturus Fructus, and Honey-fried Licorice Root in equal proportions. Si-Ni-San can alleviate liver injury through protecting hepatocyte membranes, increasing NO release and facilitating apoptosis of liver-infiltrating cells[14], and modified Si-Ni-San also has hepatoprotective effects[15]. Moreover, glycyrrhizin[16] and paeoniflorin[17], two components of Si-Ni-San, have shown beneficial effects on NAFLD.…”
Section: Introductionmentioning
confidence: 99%